Exclamative clauses at the syntax-semantics interface - Zanuttini, Raffaella; Portner, Paul (ZAS Papers in Linguistics, 2001)
Exclamative clauses exhibit a structural diversity which raises the question of whether they form a clause type in the sense of Sadock & Zwicky (1985). Based on data from English, Italian, and Paduan, we argue that the class of exclamatives is syntactically characterizable in terms of a pair of abstract syntactic properties. Moreover, we propose that these properties encode two components of meaning which uniquely define the semantics and pragmatics of exclarnatives. Overall, our paper is a contribution to the study of the syntaxlsemantics interface and offers a new perspective on the notion of clause type.